The Influence of Influencer Marketing, Social Media Marketing, and Campaigns on Fashion Customer Loyalty in the TikTok App (Study on Converse Brand) - Rendi Supiandi; Jefry Romdonny; Yono Maulana (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The digital age has turned TikTok Shop into a transformative phenomenon in the global e-commerce landscape, particularly in the fashion industry. TikTok Shop creates an immersive and interactive shopping experience by integrating entertainment and shopping in one ecosystem. The platform has seen significant transaction growth in Indonesia, making it one of the fastest-growing e-commerce markets. This research seeks to measure the impact that influencer marketing, promotion on social media, and campaigns on customer devotion in the fashion sector on the TikTok App, with a focus on the Converse brand. The research problem addresses the challenge of maintaining customer loyalty in a competitive digital environment where engagement and sales show alarming trends. This research uses an associative quantitative approach with a survey method using a digital questionnaire distributed through Google Forms. The sample consisted of 200 respondents who are active users of the TikTok application in Cirebon City aged 18-40 years and familiar with the Converse brand. Data collection used technique of purposive sampling, and the analyses were conducted using SPSS within validity, reliability, and the analysis of multivariate linear regression tests. The findings demonstrated that influencer marketing, promotion on social media, and campaigns have a favourable and noteworthy impact on customer devotion. Regression analysis shows that the three factors together affect the loyalty of client by 43.6%, while 56.4% is influenced by other factors outside this study. Therefore, Converse needs to continue developing innovative and interactive digital marketing strategies according to audience preferences in the digital.